Kononenko I., Mytnik I., Wasiak E. Słownik tematyczny polsko-ukrainski - Бріцин, В.; Ніколаєнко, Л. (Мовознавство, 2011)
Рецензія на книгу: Kononenko І., Mytnik І., Wasіак Έ. Słownik tematyczny polsko-ukrainski. Warszawa : Wyd-wo Naukowe PWN SA, 2010.— 550 s.